The Effect of Green Marketing, Brand Image, Store Atmosphere, and Quality of Service on Customer Loyalty at Bojongsari Starbucks - Syahnadia Zakaria; Ali Maddinsyah (Jurnal Ad'ministrare, 2022)
This study aims to analyze and prove the influences of Green Marketing, Brand Image, Store Atmosphere, and Service Quality on Customer Loyalty at Bojongsari Starbucks, either partially or simultaneously. This research applied associative approach. There were 100 respondents as samples involved in technique of determining sample. And methods of regression analysis, determination test, t-test, and f-test are used to analyze the data. From this research, there were some findings. They were green marketing showed to have a positive and significant effect on customer loyalty. This is shown by the t-count value of 8.268 and the significance value of 0.000. Brand image is proven to have a positive and significant effect on customer loyalty. This is shown by the t-count value of 7.967 and the significance value of 0.000. Still, store atmosphere is proven to have a positive and significant effect on customer loyalty, which is shown by the t-count value of 4.663 and a significance value of 0.000. The last, service quality is proven to positively and significantly affects customer loyalty. This can be seen from the t-count value of 8.839 and the significance level of 0.000. Green marketing, along with brand image, store atmosphere and service quality shows positive and significant effects on customer loyalty at Bojongsari Starbucks. This is shown by the F-count value of 33.737 and a significance value of 0.000. With an R-Square value of 0.569 which means that green marketing, brand image, store atmosphere and service quality all together can contribute to influence customer loyalty by 56.9%. This proves that if green marketing, brand image, store atmosphere and the quality of service are carried out and synergized properly, they will significantly affect the increase of customer loyalty at Bojongsari Starbucks.